Ekspresi TNF-α Histopatologi Ginjal Pada Tikus Model Sepsis Sebagai Efek Preventif Diberi Nanoemulsi Burdock Yang Diinduksi Bakteri MRSA - Faizal, Imam Agus; Nugroho, Yusuf Eko; Fauziah, Rahma Shifa; Yunadi, Frisca Dwi; Swandari, Mika Tri Kumala (Jurnal Sain Veteriner, 2026)
One of the natural ingredients utilized as a traditional medicinal herb is Arctium lappa L. or commonly called burdock. This plant has roots, leaves, seeds that have been used to treat infections and various skin disorders. Burdock is used for anti-inflammatory, anti-cancer, infection-fighting, and anti-tumor regulating activities. The purpose of this research is to determine the effect of Arctium lappa L. root extract on renal histopathology and tumor necrosis factor-alpha (TNF-α) expression in white rat sepsis model after Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria administration. Where in this research stage is divided into 5 groups of test animal treatment. Each group was injected with MRSA bacterial suspension with a standard MC Farland turbidity test of 0.5. The results of this research obtained that burdock root extract is able to inhibit inflammation of sepsis test animals caused by MRSA bacteria with the average value of TNF- α reaction presentation, namely K1 (-) (13.632; 14.756), K2 (+) (33.291; 29,568), K3 (150 mg/kg BW) (35,458; 33,273), K4 (300 mg/kg BW) (36,120; 28,731) K5 (450 mg/kg BW) (28,086; 228,084. So it can be stated that Arctium lappa L root extract is able to inhibit inflammation with the use of the most effective dose of 450 mg/kg BW.